Motivasi Santriwati dalam Pembelajaran Kitab Kuning di Pondok Pesantren Musthafawiyah Purba Baru - Abdul Sattar Daulay; Sonipah Nasution (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2021)
This research is a type of qualitative research. While the approach used in this research is qualitative and descriptive. Data collection techniques used observation, interviews, and documentation. The data analysis technique used is a qualitative method which will be presented in a descriptive form (exposure). The analytical framework used is deductive analysis, where things that are general lead to things that are special or specific. The results of this study indicate the motivation of the female students in studying the yellow book at the Musthafawiah Purba Baru Islamic Boarding School including to deepen and expand knowledge in the field of Tafsir, to deepen and expand knowledge in the field of Hadith, to master the rules of Arabic, to get good grades. , and wanted to become a religious teacher. While the function of motivation for fourth grade students of the Musthafawiah Purba Baru Islamic Boarding School in studying the Yellow Book, from 35 local groups represented by class IV local 25 totaling 38 people, including encouraging students to learn, making learning active, knowing a lot about religious sciences. Islam, and make learning outcomes better.